STUDENTS’ PERCEPTION OF KAHOOT.IT USED AS MEDIA TO ASSESS THEIR ENGLISH GRAMMAR COMPETENCE - Ilone , Nadia; Komara , Cahya; Yulinar , Niken Asri (UICELL, 2023)
This research is aimed at finding empirical data from students’ perception of Kahoot.it used by teachers to assess students’ English Grammar mastery. This research was focused on small-scale samples of senior-level students from three schools in East Jakarta. Thus, this research could crack the actual impressions of each student toward the usage of Kahoot.it particularly in the grammar assessment context. This research employed a quantitative descriptive approach by using a survey design. This research applied an online G-form instrument that consisted of 24 items with closed and open-ended questionnaire formats. There was a total of 234 students who completed the instruments. The data collection was calculated by using Microsoft Excel and SPSS 25 version. The findings clearly showed positive results towards Kahoot.it usage on the aspects of Features and Display (67.91%), Experience; Likeness and Interest (61.91%), and Grammar Assessment Tool (60.97%). These data were also supported by the result of a close-ended questionnaire which presented plenty of good statements. It is convincing to affirm Kahoot.it is truly beneficial for the students to assess their English grammar competence. learners. This research aims to expose the descriptive accounts of the teaching and learning process in online learning settings which is related to critical and creative thinking. This research will be a case study that uses observation and interview as data collection techniques. Keywords: Assessment, English Grammar, Kahoot, Perception, Students